Redescription of Alox chaunos Galil & Ng, 2007 (Crustacea: Decapoda: Brachyura: Leucosiidae) new to Japan; with notes on the male characters of A. latusoides (Sakai, 1937) - Ohtsuchi, Naoya; Kawamura, Tomohiko (Zootaxa, 2016)
The leucosiid crab Alox chaunos Galil & Ng, 2007 is reported from Japan for the first time, and redescribed on the basis of specimens from the Ryukyu Islands. The taxonomy of this species is discussed, and comparisons are made with A. rugosum (Stimpson, 1858), A. uru Naruse & Ng, 2006, and A. liklik Galil & Ng, 2015. Alox somphos Tan & Ng, 1995, is excluded from the fauna of Japan, the original record actually based on a specimen of A. chaunos. Male characters of A. latusoides are also described for the first time to differentiate this species from A. chaunos.